2016
DOI: 10.1016/j.jaci.2015.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Association between childhood eczema and headaches: An analysis of 19 US population-based studies

Abstract: Background-Atopic dermatitis (or eczema) is a chronic inflammatory disorder associated with sleep disturbances and quality-of-life impairment. Sleep disturbances have been shown to cause headaches in childhood. However, an association between eczema and headaches is not well established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…In addition, a casecontrol study in children with and without migraine demonstrated a higher risk of AD and other atopic diseases (19). Furthermore, several reports found a greater prevalence of headache and migraine in children with atopic disorders than their peers without atopic disorders (20), and a recent cross-sectional study of a large pediatric population demonstrated that children with eczema have higher odds (1.52) of having headaches (21). Our study revealed a statistical association between AD and migraine in adolescents, consistent with the association previously found in children.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, a casecontrol study in children with and without migraine demonstrated a higher risk of AD and other atopic diseases (19). Furthermore, several reports found a greater prevalence of headache and migraine in children with atopic disorders than their peers without atopic disorders (20), and a recent cross-sectional study of a large pediatric population demonstrated that children with eczema have higher odds (1.52) of having headaches (21). Our study revealed a statistical association between AD and migraine in adolescents, consistent with the association previously found in children.…”
Section: Discussionsupporting
confidence: 91%
“…Intense pruritus, high rates of sleep disturbance, stigma, social isolation, poor quality of life, and neuro-inflammation have been postulated to contribute to increased anxiety, depression, or suicidality in AD. Sleep disturbances in AD were shown to be associated with a number of poor outcomes in AD patients, including headaches, 69 shorter stature in children, 70 poor QOL in children and adults, 5,13,14,71 increased fractures and other injuries, 72 and even cardiovascular risk factors or disease in adults. 73 Fatigue and sleep disturbances may increase the risk of, or share a common mechanism with, anxiety or depression.…”
Section: Mechanismmentioning
confidence: 99%
“…Histamine modulates neurogenic inflammation and nociceptive sensitization. Eczema, where histamine is fundamental for inducing allergic inflammation, is associated with increased headaches in childhood, particularly in patients with severe disease accompanied by atopy, fatigue, and sleep disturbances . Higher migraine prevalence also is found in patients with allergic rhinitis .…”
Section: Introductionmentioning
confidence: 99%